Factors Related to Stunting Incidence in Toddlers in the Working Area of the Waborobo Health Center, Betoambari District, Baubau City in 2023 - Miftahul Rizkika; Ruwiah Ruwiah; Fithria Fithria (Journal of Social Research, 2023)
Stunting in children is the impact of nutritional deficiencies during the first thousand days of life. This causes irreversible disturbance of the child's physical development, thus causing a decrease in cognitive and motor skills and a decrease in work performance. The purpose of this study was to determine the factors associated with stunting in toddlers in the work area of the Waborobo Health Center, Betoambari District, BauBau City in 2023. The type of research used in this study was an analytic survey study by taking non-random cluster sampling using a cross-sectional study design. by using the chi-square test in the SPSS program. The population in this study was 136 people, while the sample was 99 people. The results of this study found that there was a significant relationship between energy intake (P Value = 0.011 <0.05), protein intake (P Value = 0.007 <0.05), calcium intake (P Value = 0.001 <0.05), and administration Exclusive breastfeeding (P Value = 0.001 <0.05) with stunting. The conclusions of this study show that there is a significant relationship between energy intake, protein intake, calcium intake, and exclusive breastfeeding with the incidence of stunting in toddlers in the work area of the Waborobo Health Center, Betoambari District, BauBau City in 2023. The research suggestion is that the puskesmas needs to provide personal education to pregnant women and mothers with toddlers regarding the importance of nutritional intake during pregnancy and the toddler's growth period, as well as providing education regarding the nutritional status of toddlers, especially stunting, to the community or cadres.